Prevalence Of Parafunctional Habits And Temporomandibular Disorder Symptoms In Young Individuals Reporting To Watim Dental Hospital - Khan, Aleshba Saba; Sana, Aleeza; Sufian, Zarah; Afreen, Ammarah; Shakoor, Asma; Shuja, Eruj (Journal of Rawalpindi Medical College, 2023)
Objective: This study aims to identify the prevalence of parafunctional habits and common symptoms of temporomandibular disorders in young individuals reporting to the Watim Dental College Materials and methods: This cross-sectional study was carried out by a survey and clinical examination over a period of six months from September 2021 to February 2022. Data from 103 patients, who fulfilled the inclusion criteria, were collected using a structured questionnaire and clinical examination regarding their parafunctional habits and temporomandibular joint symptoms. Informed consent was filled out by all the participants. Data were analyzed using SPSS version 23. A descriptive analysis was calculated for both quantitative and qualitative variables. Results: The prevalence of oral parafunctional habits among the study sample was quantified on a binary scale (yes/no) where nail-biting was observed to be highly prevalent (38%), followed by mouth breathing (27%). The most frequently reported temporomandibular joint symptom was noise (clicking or crepitation) which was 66%. Difficulty in mouth opening was the least common (20%) of all the symptoms noted. Conclusion: It may be concluded from our study that amongst parafunctional habits nail biting is the most common habit amongst young individuals and amongst the temporomandibular joint disorder clicking and crepitation is the most common symptom persistent with the condition. Keywords: clicking, nail-biting, parafunctional habits, temporomandibular joint symptoms